THE ROLE OF RESTAURANT TAX ON REGIONAL INCOME IN YOGYAKARTA - Merdi Dwi Antoro; Natasya Putri Wulandari; Galih Wicaksono; Abid Imanul Akmal (Gapenas Publisher, 2023)
This study aims to determine the role of restaurant tax on local revenue, namely through measuring the effectiveness and contribution of restaurant tax to local revenue in the city of Yogyakarta. The method used for this research is to use a quantitative approach, by analyzing how much effectiveness and contribution is from 2019-2021 with secondary data taken through a website managed by the Regional Planning Development Agency (BAPPEDA) Special Region of Yogyakarta. The results of this study found that restaurant tax revenues have still fluctuated in the last 3 years, but are still in the very effective category. Meanwhile, the contribution to PAD is still in the less category